Reconstruction of Periorbital Soft Tissue Defects - Berli, Jens U.; Merbs, Shannath L.; Grant, Michael P. (Facial Plastic Surgery, 2014)
Because of the complex anatomy and fine mechanics of the periorbital soft tissues, the reconstruction of this region can be particularly daunting. Through a structured assessment of the defect, based on subunit analysis and thorough understanding of the surgical layers, we believe to allow the reconstructive surgeon to develop an algorithmic approach to these complex problems. The sequela of a suboptimal reconstruction do not only result in an inferior aesthetic result, but also have the potential for long-term functional problems such as epiphora, dry eye, ptosis, eyelid retraction, and thus requiring secondary surgery. There is no better time to aim for a perfect reconstruction than at the time of the initial surgery. In this chapter, we hope to encourage the reader to strengthen and recapitulate these analytical skills and present the most commonly used and studied techniques to help achieve a reproducible functional and aesthetically appealing result.
Keywords: periorbital; soft tissue; reconstruction; eyelid; lacrimal